Hello people,
i need a bit of help with these proofs, its one of those things were i can't sport what to do with the thing next.
1) f(x)=2x +lnx, g(x) = e^2x, prove that gf(x)=4e^4x
2) (cosec x)^4 - (cot x)^4 = (cosec x )^2 + (cot x)^2
3)
P= (2800ae^0.2t)/(1 +ae^0.2t) a=0.12
show that p = 336/(0.12 + e^-0.2t)
P = (2800ae^0.2t)/(1 +ae^0.2t) .............................. plug in a = 0.12
=> P = [2800(0.12)e^(0.2t)]/[1 + 0.12e^(0.2t)] ..........now simplify
=> P = [336e^(0.2t)]/[1 + 0.12e^(0.2t)]
=> P = 336/{e^(-0.2t)[1 + 0.12e^(0.2t)]}
=> P = 336/[0.12e^(0.2t) * e^(-0.2t) + e^(-0.2t)]
=> P = 336/(0.12 + e^-0.2t)